Dynamic behavior analysis of a moving coil oil-free linear compressor in refrigeration system. (January 2022) - Li, Chengzhan; Zou, Huiming; Cai, Jinghui; Jiang, Yuyan; Guo, Chaohong
Abstract: Linear compressor has received continuous attention owing to its high energy conversion efficiency and oil-free operation. The dynamic behavior of a linear compressor is critical to understand its operation mechanism. However, the dynamic behavior of linear compressor cannot be fully visible. In response to this issue, a real-time measurement system is established to analyze the dynamic behavior of linear motor, piston and valve movements and the cylinder pressure. And deprived effects of gas force, i.e., piston offset and leakage are also discussed. The results show that current/displacement curves generate distortion on account of the nonlinear characteristic of gas force. Distortion of current curves (THD is up to 73.69% at 60 Hz) is more obvious due to the minor inductance. The valve appears delay opening, flutter, additional displacement fluctuation and delay closing compared with ideal valve. A high spring stiffness of valve makes slight difference to piston offset. The expansion/compression index in the p -V diagram with a high frequency has apparent increase owing to the variations of duration of heat exchange. The piston offset is nearly constant with the increasing of strokes while piston offset increases with the increment of discharge pressure/frequency. The leakage loss proportion with evaporation temperature at 5 °C and condensation temperature at 30∼40 °C does not exceed 6%.